Budgeting in Switzerland - Kraan, Dirk-Jan (OECD Publishing, 2006)
The Swiss budgeting system is characterised by three special features: the political environment; the debt containment rule; and the nature of the federal budget as a transfer budget. Prominent features of the political environment are direct democracy, consensus and federalism